A Pilot Study of Small-Diameter One-Piece Ceramic Implants Placed in Anterior Regions: Clinical and Esthetic Outcomes at 1-Year Follow-up. - Kunavisarut, Chatchai; Buranajanyakul, Leerawan; Kitisubkanchana, Jira; Pumpaluk, Piyapanna (International Journal of Oral & Maxillofacial Implants)
Purpose: The aim of this study was to evaluate the clinical, esthetic, and patient-reported outcomes of one-piece zirconia implants placed in incisal areas using digital surgical templates after 1 year of follow-up. Materials and Methods: Patients who had lost an anterior tooth received a 3.3-mm-diameter zirconia implant placed by computer-guided surgery. Implant survival and soft tissue conditions were assessed periodically 1 week, 3 months, 6 months, and 1 year after loading. Standardized radiographs were taken at definitive prosthesis insertion and 1 year postloading to evaluate peri-implant bone loss. Additionally, the esthetic outcomes and patient-reported outcomes were also investigated. Results: Twenty zirconia implants were placed in 20 patients with no implants lost, resulting in 100% survival rates. A minor change in the mean marginal bone level (0.14 ± 0.87 mm) was found between definitive prosthetic loading and 12 months later. Periimplant soft tissue remained stable throughout the observation period. The mean Pink Esthetic Score and White Esthetic Score were 12.05 and 8.60, respectively, while the mean Gingival Papilla Index scores were 1.55 at the mesial papilla and 1.65 at the distal papilla at the 1-year follow-up. The mean visual analog scale scores for patient perception of the overall process, speech, mastication, and esthetics were 93.3 ± 7.8, 95.1 ± 5.3, 93.6 ± 7.6, and 94.5 ± 6.2 mm, respectively. Conclusion: For the 1-year results, 3.3-mm-diameter one-piece ceramic implants placed by computer-guided surgery showed favorable clinical performances with no failure when used for single-tooth replacement in anterior regions.